Long-term analysis of drinking water quality in poultry and pig farms in Northwest Germany - Münster, Pia; Kemper, Nicole (Frontiers in Animal Science, 2024)
Hygienically safe drinking water is essential for the health, well-being, and efficient production of livestock. In contrast to drinking water for human consumption, there are guidelines but no legal limits for drinking water for animals. Risk factors due to hygienically relevant microorganisms or chemical compounds in drinking water are known from literature, but there is little information on the quality of drinking water for livestock in Germany. To gain an overview of the quality of drinking water, data from samples collected from pig and poultry farms in Northwest Germany over a 10-year period were analyzed retrospectively. Data consisted of 326 samples analyzed chemically, and 519 samples analyzed microbiologically. Of these, 80 water samples were analyzed for both chemical and microbial contaminants. There was no correlation between samples exceeding chemical and microbial guideline levels. The number of samples exceeding the chemical guideline values (58.0%) was higher than the number of samples exceeding the microbiological guideline values (47.4%). This long-term study illustrated the potential risk to pigs and poultry from drinking water and highlights the need for effective hygiene measures to prevent the transmission of microorganisms and chemicals residues through water to maintain animal health and safe food products.